IMPROVING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION BY USING KNOW-WANT-LEARN (KWL) CHART TECHNIQUE - Novita Husna Nasution (TRANSFORM : Journal of English Language Teaching and Learning, 2012)
This study focuses on the process of improving students’ achievement in reading comprehension by using KWL Chart Technique. The objective was to discover the significant improvement of students’ achievement in reading comprehension when the students were taught by using KWL Chart Technique. The subjects of the study were the second grade students of SMP Negeri 29 Medan. There were thirty four students. They were taught by using KWL Chart Technique. The instruments for the data collection were reading assessment, questionnaire sheet, and observation sheet. The techniques of the data analysis applied were quantitative and qualitative. In analyzing the data, the students were three reading tests namely orientation test, test I, and test II. The mean of students’ core for the orientation test was 38.59, test I was 59.32, and test II was 77.76. The total percentage of students who passed the passing grade significantly improved, in the orientation test it was 3.12%, in test I it was 23.53%, and in test II it was 88.24%. It was found that the application of KWL Chart Technique significantly improved the students’ achievement in reading comprehension.   Key Words: Know-Want-Learn (KWL), reading comprehension